Reseña de: Beltrán, E.M.; Orduña, F.J. y Campuzano, A.B. (dirs.). (2012). Curso de derecho privado. Valencia: Tirant Lo Blanch, Valencia, 773 p. - Muñoz Catalán, Elisa (Revista de Humanidades, 2013)
Reseña de libro